Accelerated Hypofractionated Radiation Therapy for Elderly Frail Bladder Cancer Patients Unfit for Surgery or Chemotherapy. (February 2019) - Hammer, Liat; Laufer, Menahem; Dotan, Zohar; Leibowitz-Amit, Raya; Berger, Raanan; Felder, Shira; Weiss, Ilana; Lawrence, Yaacov Richard; Symon, Zvi
Abstract : Purpose/Objectives: The main purpose of this study was to report treatment outcomes of definitive image-guided accelerated hypofractionated radiation therapy for elderly patients with muscle-invasive bladder cancer unsuitable for surgery or trimodality therapy. Materials and Methods: Patients with confirmed muscle-invasive or high-risk T1 transitional cell carcinoma of the bladder, stage T1-T4aN0M0, who underwent transurethral resection of bladder tumor were irradiated with 45 Gy in 15 fractions. Comorbidity was assessed by Charlson Comorbidity Index. Cystoscopy, cytology, and computerised tomography imaging were used to evaluate treatment outcomes. Results: Seventeen patients with a median age of 87 (range, 81 to 95) years and age-adjusted Charlson Comorbidity Index ≥3 were included. Transurethral resection of bladder tumor was incomplete in 65%. Radiation technique evolved from 3-dimensional conformal radiotherapy (3D CRT, 47%) to volumetric modulated arc therapy (VMAT, 53%). Ninety-four percent completed radiotherapy, with a median time of 20 days. The median follow-up was 65.3 months. Complete local response at 3-month cystoscopy was 69%. Six patients developed a local recurrence (35%), and 2 patients developed distant metastases (11.7%). Overall survival at 1 year was 47% and 23% at 2 years. Cancer-specific survival at 1 and 2 years were 85% and 63%, respectively. Acute grade 3 gastrointestinal or genitourinary toxicities were 6% and 24%, respectively. No grade 4 toxicity was documented. Diarrhea of any grade occurred in 35% of patients treated with 3D CRT, but in none of the patients treated with VMAT ( P =0.002). Conclusions: Accelerated hypofractionated radiotherapy alone provides good local control in elderly patients unfit for chemoradiotherapy. Contemporary radiation techniques such as VMAT were associated with reduced bowel toxicity compared with 3D CRT.